2023
DOI: 10.37934/arfmts.104.1.185203
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cone Angle on Surface Pressure Distribution along Slant Length of a Cone at Hypersonic Mach Numbers

Abstract: In the present study, the prime attention is to numerically simulate the surface pressure distribution over the slant length of the cone at the various Mach numbers and for the considerable range of semi-cone angles. The Computational Fluid Dynamics (CFD) analysis is used to simulate the surface pressure distribution numerically. The hypersonic Mach numbers, semi-cone angle, and various locations along the slant length of a cone are considered parameters for this research work. The Mach numbers (M) considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Analytical studies utilizing Computational Fluid Dynamics (CFD) analysis have meticulously examined external flows over 2D wedges, 3D cones, and catalytic converters, yielding promising results [17][18][19]. CFD analysis is widely used in various applications and similar studies have been found in the literature using CFD analysis [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical studies utilizing Computational Fluid Dynamics (CFD) analysis have meticulously examined external flows over 2D wedges, 3D cones, and catalytic converters, yielding promising results [17][18][19]. CFD analysis is widely used in various applications and similar studies have been found in the literature using CFD analysis [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%